Dinâmicas de mudança e continuidade em contextos de crise: estudo de caso em organização híbrida - Guerra, Rafael Prado (2017)
The present study intends to analyze dynamics of change and continuity in crisis contexts, through a case study of a hybrid organization of the energy sector in an emerging country. It is investigated the recent creation process of the Controlling area (until then formally nonexistent), from a historical perspective of agency-structure, trying to identify hybrid dynamics and strategies of resistance-acceptance to the imposition of a new order, resulting from the exchange of management and organizational restructuring. Qualitative research methods were used, using in-depth interviews with the company high-level executives, through a semi-structured and open questions script, as well as documentary and bibliographic analysis of primary and secondary sources. It can be observed that the scenario of institutional and economic crisis through which the organization, the sector and the country were passing made possible the emergence of managerialist logics and financial perspectives, accelerating the processes of changes that were already underway. However, we observed resistance actions that reshaped the initially proposed design for organizational restructuring referenced to market benchmarks, in which interaction and negotiation between agents promoted hybridization processes of structures and strategies that re-adjusted the final configuration. The work approach can be characterized as a limiting factor in hindering a more active and prolific participation of the interviewees, since in addressing sensitive issues such as restructuring, strategy, changes, acceptance, resistance, among others, they may worry about preserving information secrecy, strategic data or specific knowledge for the organization, and in certain cases there may be a selectivity criterion regarding the responses granted. It contributes to the practice because it allows the understanding of acceptance-resistance dynamics to organizational change and the resolutions arising from the social interaction of agents in the corporate environment, as a way of providing subsidies to managers of hybrid organizations belonging to this and other sectors and countries. It also adds to the theory evidence regarding research linked to the critical perspective, in that it brings important elements and field data to academic discussion.